P4-ATPases: how an old dog learnt new tricks — structure and mechanism of lipid flippases. (August 2020) - Lyons, Joseph A; Timcenko, Milena; Dieudonné, Thibaud; Lenoir, Guillaume; Nissen, Poul
Highlights: P4-ATPase drive the transport of phospholipids directed to the cytoplasmic leaflet. Structures for yeast and human P4-ATPases have been determined by cryo-electron microscopy. P4-ATPases are autoregulated by direct interactions between the C-terminus and ATPase domains, which also gates lipid access. Future work must address the structural determinants of substrate specificity and release. Abstract : Type 4 P-type ATPases (P4-ATPases) are lipid flippases that drive the active, inward directed translocation (flip) of lipids in eukaryotic membranes. The resulting lipid asymmetry potentiates the membrane and is essential for a wide range of cellular processes such as vesicle biogenesis and trafficking and membrane protein regulation, whereas dissipation of lipid asymmetry is required in blood coagulation and apoptosis. Through recent advances in cryo-electron microscopy, several landmark structures of yeast and human lipid flippases have been reported, highlighting the similarities and differences they share with the cation transporting P-type ATPases. Here, we discuss the recent lipid flippase structures in the context of subunit architecture and organization, auto-regulation and lipid transport.